E-learning environments as niche strategy to match the 'DNA' of a particular university - Lugmayr, Artur (CEUR-WS, 2013)
Currently many eLearning platforms exist that are offered by other universities which are simply deploying eLearning technologies as media streams or online courses. The clear aim of this position paper is to find the essence where diverse universities will be able to compete on the education market in the digital future by reducing teaching costs, finding an innovative model fitting to specific strategies and especially the "DNA" of the university: strategies, industrial collaboration, departments, student needs, and administration. An adaptation of existing solutions shall be avoided to find a particular digital education profile in the field of the university context. Education by extended the existing BSc., MSc. and PhD. studies. The outcome of the presentation shall be: 1) a strategy discussion for the next 5-10 years; 2) presentation of reference pilots of introducing eLearning environments within 3 online courses that were conducted previously; and 3) a presentation of a setup test-platform and curriculum that shall extend courses step-by-step towards a fully new digital eLearning experience.